2021
DOI: 10.3389/fcell.2021.671475
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cell Death in Cellular Processes During Odontogenesis

Abstract: The development of a tooth germ in a precise size, shape, and position in the jaw, involves meticulous regulation of cell proliferation and cell death. Apoptosis, as the most common type of programmed cell death during embryonic development, plays a number of key roles during odontogenesis, ranging from the budding of the oral epithelium during tooth initiation, to later tooth germ morphogenesis and removal of enamel knot signaling center. Here, we summarize recent knowledge about the distribution and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 252 publications
(407 reference statements)
0
9
0
Order By: Relevance
“…41 Previous reports have also identified odontoblast apoptosis during odontogenesis. 42–44 However, these studies have identified cell apoptosis in stages before initial mineralization, i.e. , at E12–E13, and have associated the cell fate with molecular signaling including the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Previous reports have also identified odontoblast apoptosis during odontogenesis. 42–44 However, these studies have identified cell apoptosis in stages before initial mineralization, i.e. , at E12–E13, and have associated the cell fate with molecular signaling including the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…41 Previous reports have also identified odontoblast apoptosis during odontogenesis. [42][43][44] However, these studies have identified cell apoptosis in stages before initial mineralization, i.e., at E12-E13, and have associated the cell fate with molecular signaling including the autophagic pathway. 42,43 On the other hand, our results indicated the involvement of cell membrane components, identified by annexin V immunostaining, as initiators of early dentin mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 IK is silenced via apoptosis at the bud stage. 5,52 IK with specific Eda and NFkB signalling was originally observed in the incisors, and its size affects the incisor germ size. 53 The molar IK has high expression of Wnt and Shh, and interference of IK formation via physical ablation or Wnt signal confusion can prevent the development of the tooth germ.…”
Section: Tooth Region Determinationmentioning
confidence: 99%
“…Interactions between epithelium and the underlying mesenchyme play important roles for development of tooth from bud, cap, bell to secretory stages ( Santosh and Jones, 2014 ; Balic, 2018 ). At cap stage, enamel knot (EK), a non-proliferating signaling center of tooth development closely linked with epithelial-mesenchymal interactions, expresses important signaling molecules including autocrine and paracrine factors, and transcription factors for proper tooth morphogenesis ( Yu and Klein, 2020 ; Abramyan et al, 2021 ). At the secretory stage, inner enamel epithelium (IEE) begins differentiate into ameloblasts and the underlying mesenchymal dental papilla (DP) differentiate into odontoblasts for the secretion of enamel and dentin respectively ( Otsu et al, 2011 ; Kawashima and Okiji, 2016 ).…”
Section: Introductionmentioning
confidence: 99%